Differential active site requirements for NDM-1 β-lactamase hydrolysis of carbapenem versus penicillin and cephalosporin antibiotics. Issue 1 (December 2018) - Sun, Zhizeng; Hu, Liya; Sankaran, Banumathi; Prasad, B.; Palzkill, Timothy
Abstract New Delhi metallo-β-lactamase-1 exhibits a broad substrate profile for hydrolysis of the penicillin, cephalosporin and 'last resort' carbapenems, and thus confers bacterial resistance to nearly all β-lactam antibiotics. Here we address whether the high catalytic efficiency for hydrolysis of these diverse substrates is reflected by similar sequence and structural requirements for catalysis, i.e., whether the same catalytic machinery is used to achieve hydrolysis of each class. Deep sequencing of randomized single codon mutation libraries that were selected for resistance to representative antibiotics reveal stringent sequence requirements for carbapenem versus penicillin or cephalosporin hydrolysis. Further, the residue positions required for hydrolysis of penicillins and cephalosporins are a subset of those required for carbapenem hydrolysis. Thus, while a common core of residues is used for catalysis of all substrates, carbapenem hydrolysis requires an additional set of residues to achieve catalytic efficiency comparable to that for penicillins and cephalosporins. The NDM-1 β-lactamase confers resistance to most β-lactam antibiotics. By functional analysis of residues required for hydrolysis, Sun et al. reveal stringent sequence constraints for carbapenems, suggesting that specific combinations of NDM-1 inhibitors might help reducing resistance development